Improving LSPR sensing performance using multilayered composition graded Ag–Cu nanotriangle arrays. Issue 9 (14th January 2019) - Larson, Steven; Yang, Zilan; Zhao, Yiping
Abstract : We demonstrate a novel deposition strategy for graded nanotriangle arrays, showing that graded boundaries can improve plasmon resonance sensing. Abstract : Patterned nanotriangle arrays with composition graded and multilayered Ag–Cu were fabricated by a co-deposition and nanosphere lithography process. With the increase of the number of layers or constructing a continuum graded layer, the index sensitivity of the resulting nanotriangles kept on increasing, indicating that the graded boundaries can improve plasmon resonance sensing.